2004
DOI: 10.1590/s0034-71402004000200002
|View full text |Cite
|
Sign up to set email alerts
|

Filiação industrial e diferencial de salários no Brasil

Abstract: Este artigo investiga os diferenciais de salários inter-industriais no Brasil. Os efeitos da filiação industrial nos salários foram examinados ao nível de três dígitos, e foram utilizadas variáveis de controle associadasàs firmas como tamanho das plantas, nacionalidade do capital e acesso ao mercado internacional, além de variáveis associadas aos trabalhadores. Dessa forma, foi possível a estimação dos prêmios salariais industriais considerando tanto características da oferta como, também, da demanda de trabal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 35 publications
0
8
0
7
Order By: Relevance
“…This finding agrees with Reis and Camargo (2007), who argue that the recent inflation stabilization has increased the real wage rigidity because inflation imposes more flexibility to the real wage in situations where the nominal wage is not legally allowed to be reduced. Results by Arbache and De Negri (2004) and Orellano et al (2009), using micro-data, also suggest that the Brazilian wage structure is rigid and insensitive to the economic cycle.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This finding agrees with Reis and Camargo (2007), who argue that the recent inflation stabilization has increased the real wage rigidity because inflation imposes more flexibility to the real wage in situations where the nominal wage is not legally allowed to be reduced. Results by Arbache and De Negri (2004) and Orellano et al (2009), using micro-data, also suggest that the Brazilian wage structure is rigid and insensitive to the economic cycle.…”
Section: Discussionmentioning
confidence: 88%
“…Apart from methodological and empirical differences, that high degree of wage rigidity is in line with other studies for the Brazilian economy. Arbache and De Negri (2004) investigated the inter-industry wages in Brazil and found high stability of wage awards, suggesting that the wage structure is rigid and insensitive to the economic cycle. Orellano et al (2009) showed that the replacement rate of workers by Brazilian firms as a tool to reduce wages has decreased with inflation decline.…”
Section: Introductionmentioning
confidence: 99%
“…This could result from the association of hazardous exposures with less skilled and lower wage jobs,6 and weaker labour protection enforcement among small enterprises,10 25 where lower wage jobs are more common 26. The incidence and incidence density rates demonstrated even greater safety disparities among low-income women than low-income men.…”
Section: Discussionmentioning
confidence: 99%
“…Para os autores, a inflação impõe mais flexibilidade aos salários reais, tendo em vista ao ambiente legal, em que não é permitido a redução o salário nominal. Arbache & De Negri (2004) e Orellano et al (2009), usando micro-dados, sugerem também que estrutura de salários brasileiros é rígida e insensível ao ciclo econômico. Mazali & Divino (2010) mostram ainda que a estimativa do trade-off de curto prazo indicou que um choque 1% na oferta monetária, o banco central deve escolher entre uma queda de 0,29% no hiato do produto, mantendo o mesmo nível de inflação, ou elevar a inflação em 0,31% e manter fixo o hiato do produto.…”
Section: A Curva De Phillips E Evidências Para Economia Brasileiraunclassified